Optimasi Pola Operasi Waduk Untuk Memenuhi Kebutuhan Energi Pembangkit Listrik Tenaga Air (Studi Kasus Waduk Wonogiri) - Samosir, Cahaya Santoso; Soetopo, Widandi; Yuliani, Emma (Fakultas Teknik, Universitas Brawijaya, 2015)
The reservoir is expected to utilize water into the source of energy using hidroelectric power plants. Unfortunately, there is reduction of its function time by time because of sedimentation problem at the bottom of Wonogiri reservoir. Because of this problem, there are urgent needs of good management, planning, and operation to optimize the Wonogiri function again. One of the effective methods is the application of stochastic operational simulation rule of reservoir assisted with solver evolutionary program. Based on analysis result, the application of optimization operational simulation rule using stochastic model had better electric production than existing operational simulation rule. There was the increase of electric production as much as 22.98% (77.733 MWh/15days) from 33,820 MWh/15days to 41,593 MWh/15days. The performance evaluation showed that the reservoir had a 100% reliability to produce electricity and 80% to fulfill water demand in downstream area.Keywords: Wonogiri reservoir, reservoir operation rule, simulation, stochastic model, reservoir evaluation